PENCEGAHAN KEKERASAN SEKSUAL MELALUI PENDIDIKAN KESADARAN TUBUH BAGI ANAK DISABILITAS INTELEKTUAL DI SLB C YPAC PALEMBANG - Sari, Yona Wia Sartika; Anggraini, Rini; Kesuma, Anggun; Safana, Hanifatus; Gumay, Nabila Putri; Safitri, Nazila; Nada, Rahma Haifa; Ermi, Nurmalia; Tindaon, Rotua Lenawati (Universitas Sanata Dharma, 2025)
Children with disabilities have equal rights to education, including reproductive health education. However, physical, cognitive, and sensory limitations can hinder their understanding of body awareness and personal boundaries. This study aimed to provide knowledge about body parts and prevent sexual violence among children with intellectual disabilities. This activity was conducted at the Special School C Foundation for the Development of Disabled Children (Sekolah Luar Biasa C Yayasan Pembinaan Anak Cacat or SLB C YPAC Palembang) on April 29, 2025, involving five sixth-grade students. Methods included using human body illustrations, sticky notes, the song “Ku Jaga Diriku,” and body movements. Observations showed that most participants were able to distinguish between appropriate and inappropriate touch, despite challenges in attention and communication. The role of the mentoring teacher was essential in supporting student engagement and comprehension. This form of education is considered beneficial and can be integrated into school learning.